About the facture of artistic texts - Myroshnychenko, Maria Pavlivna (My University, 2021)
The reality is reflected in the artistic text according to two principles of reflection: the principle of projectivity (the similarity to reality is shown at the level of a concrete image, for example, in realistic painting or in a photo) and the principle of conceptuality (the similarity to reality is observed at the level of understanding, of connections between images). Facture as a category of esthetics was originally considered as a characteristic of projective texts. Any verbal text refers to texts that are predominantly conceptual. However, verbal texts in the process of reading "grow in meanings" in the consciousness of the recipients, i.e. generate "subject" images and connections between them. The fact that the "subject" images of the verbal text are more distant from the author's original plan cannot be the reason for refusing to analyze the originality of the facture of the work in its various aspects, including as one of the essential feature of writing style. The study of the musical nature of the verbal text, as well as its visual features (details, realism, volume, contrast system, speech figures) provides a clue about facture of the artistic world of the work, as well as due to how, in particular, the facture of a text or writing style of the author is formed.
Keywords: facture; artistic text; projective; conceptual; specific image